Cochlear Implant Outcomes in CHARGE Syndrome: Updated Perspectives. Issue 6 (July 2022) - Kay-Rivest, Emily; McMenomey, Sean O.; Jethanamest, Daniel; Thomas Roland, J.; Shapiro, William H.; Waltzman, Susan B.; Friedmann, David R.
Abstract : Objective: To evaluate outcomes of auditory implants in children with CHARGE syndrome and describe the evolution in management of hearing loss in this complex population. Methods: A retrospective case review was performed at a tertiary referral center. Children with CHARGE syndrome who received either a cochlear implant (CI) or auditory brainstem implant (ABI) were included. Clinical records, demographic information, CHARGE features, neuroimaging, audiology, hearing rehabilitation interventions, operative notes, and outcomes were reviewed. Results: Thirteen children with CHARGE syndrome underwent a total of 19 cochlear implants between 2008 and 2020. Among the congenitally deafened children (n = 9), six underwent bilateral implantation (five simultaneous and one sequential). Bilateral implantation was performed even in the presence of diminutive-appearing cochlear nerves. The average age of implantation was 1.1 years, and the mean device use time was 9.4 hours per day. Patients showed improvements in subjective family assessment related to hearing. In this group, two patients use oral communication, five use total communication, and two use sign language exclusively. Among the children with progressive hearing loss, the mean age of hearing deterioration was 4.4 years of age, and the device use time on average was 9.8 hours per day. The highest performer in the cohort was a child who lost hearing in their only hearing ear at age 4 and had normal cochleovestibular anatomy on that side. One child received an auditory brainstem implant at age two after deriving no benefit from a CI and can detect environmental sounds but is currently a nonuser. Over time, we noted that implantation occurred earlier in life and that practice has shifted toward bilateral implantation. Conclusions: Compared to a previous institutional cohort, children evaluated in this study were often implanted at a younger age and bilaterally with significantly improved outcomes. A CI evaluation should be considered in children with CHARGE syndrome to maximize sensory input and auditory ability.